2019
DOI: 10.2147/dmso.s194688
|View full text |Cite
|
Sign up to set email alerts
|

<p>Empagliflozin in type 1 diabetes</p>

Abstract: There is a clear unmet need in people living with type 1 diabetes (T1D). Although the quality of life of people with T1D has improved, issues like hypoglycemia, weight gain and variability in glucose profiles remain. In this review, the clinical efficacy and safety of empagliflozin, a sodium-glucose cotransporter type 2 (SGLT2) inhibitor in T1D, is described based on a review of phase 2 and 3 studies to date. Empagliflozin and SGLT2 inhibitors, in general, are effective glucose-lowering drugs, which also work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 25 publications
0
15
0
1
Order By: Relevance
“… 32 , 33 In type 1 diabetes, it has been reported that empagliflozin reduced arterial stiffness. 34 Presumably, this reduction is related to the improved arterial compliance and weight loss. In T2D, empagliflozin has been shown to improve arterial stiffness and vascular resistance.…”
Section: Possible Mechanisms Of Cardiovascular Benefitsmentioning
confidence: 99%
“… 32 , 33 In type 1 diabetes, it has been reported that empagliflozin reduced arterial stiffness. 34 Presumably, this reduction is related to the improved arterial compliance and weight loss. In T2D, empagliflozin has been shown to improve arterial stiffness and vascular resistance.…”
Section: Possible Mechanisms Of Cardiovascular Benefitsmentioning
confidence: 99%
“…The critical Ising model is described in the context of CFT by the minimal model defined by (p, p ) = (4, 3) 17,18 . A brief review of the general properties of the minimal models is included in Appendix A.…”
Section: A Ising Model In a Transverse Fieldmentioning
confidence: 99%
“…The model is critical and integrable for h = J. The critical theory is again described by a mininimal model of CFT with (p, p ) = (6, 5) 18,23,24 . Its central charge is given by c = 4/5.…”
Section: B the Quantum Three-state Potts Modelmentioning
confidence: 99%
See 2 more Smart Citations